Predictive modelling : flight delays and associated factors hartsfield–Jackson Atlanta international airport - Feiteira, Inês Viana (2018)
Project Work presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence